Remarks at the International Conference on Democracy, Market Economy, and Development - Wolfensohn, James D. (2017)
James D. Wolfensohn, President of the World Bank Group, discussed what the Bank learned in coming to look at the issues of poverty and development. Development requires proper economic policies, but also the essential element of the social aspects and human aspects of society. The Bank’s focus is to think first in terms of poverty—fighting poverty with passion was adopted recently as the first line of our mission statement. Wolfensohn discussed an agenda for action on the issues of inclusion, corruption, transparency, education, knowledge, and private sector environment. How we attack this agenda must be a partnership between governments, multilaterals, such as the Bank, and the bilateral institutions, the private sector, and civil society in all its forms—from non-government organizations (NGOs) to trade unions, from religions to foundations, from spokesmen for ordinary people.